Planning Strategies for Community Wildfire Defense Design in Florida - Robert Brzuszek; Jason Walker; Timothy Schauwecker; Chris Campany; Marc Foster; Steve Grado (Journal of Forestry, 2010)
New community developments in the wildland-urban interface can be planned to minimize loss of property and life to wildfire through multiple defensive strategies. This research examines three communities impacted by the 1998 Florida wildfires and compares the physical context and development patterns of these communities to three recently designed Florida subdivisions that incorporate Firewise principles. Analysis of the relationship of wildfires to the physical context and development patterns of affected residential communities provides the framework by which the two groups of communities are compared. Findings show that incorporating multiple defensive strategies in community planning, including taking advantage of road location, utility corridors, greenbelts, and existing wetlands, may be effective in wildfire defense. The comparative analysis concludes with design and layout considerations for community development in the southeastern United States.